The last guardian - Colfer, Eoin (New York : Disney*Hyperion, 2012)
"Teenage genius Artemis Fowl and his arch rival Opal battle to the last in this eighth and final book in series"--
Keywords: Fowl, Artemis (Fictitious character); Adventure and adventurers; Space and time; Fairies; Magic; Genius; Juvenile Fiction -- General; Juvenile Fiction -- Action & Adventure; Juvenile Fiction -- Fantasy & Magic; Fantasy fiction; Young adult fiction